ANALISIS KINERJA OPERASI ANGKUTAN KOTA KECAMATAN CIAMIS KABUPATEN CIAMIS PROPINSI JAWA BARAT - Hartati, Gini; Defiana, Yanti; Sumarno, Wahyu (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
ABSTRACT City transportation as part of public transportation plays an important role in supporting the mobility of residents of the City of Ciamis. City transportation has the most number of fleets compared to other types of public transportation. The population itself continues to increase over time. This condition causes an increase in population mobility so that the existence of city transportation can help people's activities and mobility in their daily lives. In this study, an analysis of the performance of urban transport operations in the city of Ciamis was carried out, the aim was to determine the success of procuring urban transportation for the benefit of operators and users. Performance measurement is carried out using indicators of passenger waiting time, vehicle speed, density, headway and passenger load factor. The standard time between or headway is 1-12 minutes and the waiting time for passengers is an average of 5-10 minutes and a maximum time of 10-20 minutes refers to the standard determined by the Directorate General of Land Transportation. Based on the results of research on the headway value used in city transportation from each route, the average time interval between the first vehicle and the next vehicle is currently quite effective because it is still within the tolerance limits of the Department of Transportation regulations, which is 1-12 minutes, while the average headway City transportation is 3 minutes. The performance of city transportation when viewed in terms of efficiency and effectiveness from the survey results, city transportation at the Ciamis Terminal is quite good